Decision Support System for Determining Promotion Using a Combination of Entropy and Weighted Aggregated Sum Product Assessment - Yudhistira, Aditia; Rahmanto, Yuri; Pasaribu, A. Ferico Octaviansyah; Yasin, Ikbal; Aldino, Ahmad Ari; Setiawansyah, Setiawansyah (Jurnal Ilmiah FIFO, 2025)
Decision-making in determining employee promotions often faces challenges due to the subjectivity of assessments. To address this issue, this research develops a decision support system by combining the Entropy method and the Weighted Aggregated Sum Product Assessment (WASPAS). The Entropy method is used to objectively determine the weights of criteria based on data variation, while the WASPAS method is applied to comprehensively rank alternatives through the integration of the Weighted Sum Model (WSM) and Weighted Product Model (WPM). The test results on seven candidates showed that Candidate A-016 ranked first with a score of 0.9733, followed by Candidate A-013 with a score of 0.7454, and Candidate A-011 with a score of 0.5386. Meanwhile, the candidate with the lowest score was Candidate A-017 with a value of 0.3456. These findings prove that the combination of Entropy and WASPAS methods can produce a more objective, transparent, and solid basis for management to make fair and rational decisions in the promotion process.